This is not the last wave of COVID-19, it seems to be. - Piryani, Rano Mal; Piryani, Suneel; Devrajani, Bikha Ram (Journal of Liaquat University of Medical & Health Sciences, 2021)
Presently, several countries are facing third wave of COVID-19 pandemic while others second; most of the countries are passing through the different stages of second or third wave with varying degree of intensity. Pakistan faces the third wave of SARS CoV-2 infection. Number of the new reported cases and deaths are rapidly rising. Though the vaccination drive has started but the pace is very slow. The Third wave may further hamper the drive. At this point in time less than 1% of population is immunized against COVID-19. There is long-way to get 60-70% population immunized and reach the level of herd immunity through vaccination/infection. Situation indicates this is not the last wave and raise the alarm that there may be waves to occur in future. Keywords: COVID-19, pandemic waves, Pakistan, SARS CoV-2,